2011
DOI: 10.1016/j.yjmcc.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Immune-inflammatory dysregulation modulates the incidence of progressive fibrosis and diastolic stiffness in the aging heart

Abstract: Diastolic dysfunction in the aging heart is a grave condition that challenges the life and lifestyle of a growing segment of our population. This report seeks to examine the role and interrelationship of inflammatory dysregulation in interstitial myocardial fibrosis and progressive diastolic dysfunction in aging mice. We studied a population of C57BL/6 mice that developed progressive diastolic dysfunction over 30 months of life. This progressive dysfunction was associated with increasing infiltration of CD45 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 52 publications
4
148
1
Order By: Relevance
“…12 Profibrotic cytokines IL-4 and IL-13 promote fibrocyte differentiation, whereas antifibrotic cytokines IFN-g and IL-12 inhibit its differentiation, suggesting that a complex interplay in the inflamed milieu determines the fate of bone marrow-derived fibroblasts. 13,18 In this study, we show that adiponectin regulates macrophage polarization and myeloid fibroblast formation in the kidney in response to obstructive injury. To explore the mechanisms by which adiponectin promotes the activation of bone marrow-derived fibroblasts in the kidney in response to obstructive injury, we demonstrate that adiponectin deficiency significantly reduces the gene expression of profibrotic chemokines and cytokines in obstructed kidneys compared with WT mice.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…12 Profibrotic cytokines IL-4 and IL-13 promote fibrocyte differentiation, whereas antifibrotic cytokines IFN-g and IL-12 inhibit its differentiation, suggesting that a complex interplay in the inflamed milieu determines the fate of bone marrow-derived fibroblasts. 13,18 In this study, we show that adiponectin regulates macrophage polarization and myeloid fibroblast formation in the kidney in response to obstructive injury. To explore the mechanisms by which adiponectin promotes the activation of bone marrow-derived fibroblasts in the kidney in response to obstructive injury, we demonstrate that adiponectin deficiency significantly reduces the gene expression of profibrotic chemokines and cytokines in obstructed kidneys compared with WT mice.…”
Section: Discussionmentioning
confidence: 56%
“…Our results showed that adiponectin deficiency reduced the mRNA expression of MCP-1 and CXCL16 ( Figure 4A), indicating that these chemokines contribute to accumulation of myeloid fibroblasts in the kidney. Th2 cytokines, IL-4 and IL-13, have been shown to promote M2 macrophage polarization and monocyte to fibroblast transition, 13,18,29,30 and so we measured the effect of adiponectin deficiency on the production of IL-4 and IL-13 in the kidney. The mRNA levels of IL-13 and IL-4 were markedly increased in obstructed kidneys of WT mice, whereas the increase in the mRNA levels of IL-13 and IL-4 was significantly reduced in obstructed kidneys of adiponectin KO mice ( Figure 4B).…”
Section: Adiponectin Deficiency Attenuates Profibrotic Chemokine and mentioning
confidence: 99%
See 1 more Smart Citation
“…Femalecats exhibited a reduction of IL-1, IL-2, IL-4, IL-6, IFN-γ, MMP-3 and TIMP-2 with age,in male cats this applied for IL-6, MMP-2 and TIMP-1.Conflicting results are reported for the role of immune modulatory cytokines in cardiac remodelling. In mouse models, Th2 induction resulted in reduced ventricular stiffness, and Th1 cells were involved in initiation of fibrosis and collagen crosslinking (Yu et al, 2005;, whereasanother 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 study did detecta shift from Th1 to Th2 response in old mice in association with interstitial myocardial fibrosis (Cieslik et al, 2011). We observed a reduction of all three immune modulatory markers (IL-2, IL-4,IFN-γ)with age in thefemale cats, which might be consistent with a generally reduced myocardial inflammatory response, as suggested by thereduced transcriptionof IL-1 and IL-6.Aupperle and co-authors (2011) observed reduced TIMP-2 expression in association with myocardial fibrosis in cats.In older sheep (> 8 years), rat and mouse models, higher myocardial MMP-2 and reduced TIMP-2 mRNA and protein expression, as well as cardiomyocyte hypertrophy and perivascular and interstitial fibrosis, imbalanced cardiac remodelling and impaired repair was observed (Kandalam et al, 2010;Wang et al, 2010;Horn et al, 2012;Givvimani et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…The differentiation of fibrocytes is regulated by other inflammatory cells, such as CD4 + T cells, via secretion of cytokines [17]. Profibrotic cytokines IL-4 and IL-13 promote fibrocyte differentiation, where as antifibrotic cytokines IFN-γ and IL-12 inhibit its differentiation, suggesting a complex interplay among the inflammatory cells in the inflamed milieu determines the fate of bone marrow-derived fibroblasts [18,19].…”
Section: Introductionmentioning
confidence: 99%